2017
DOI: 10.1093/jnci/djx218
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Patient Characteristics Associated With a Strong Preference to Preserve Sexual Function and Receipt of Active Surveillance

Abstract: Treatment choice may not always align with patients' preferences. These findings demonstrate opportunities to improve delivery of patient-centered care in early prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…3,16,17 However, to the best of our knowledge, the impact of different types of surgery and RT on sexual function has not been well studied to date. It is well known that for many patients, preserving QOL is of high importance in the treatment decision-making process; specifically, prior studies have demonstrated that >50% of men consider the preservation of sexual function to be important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,16,17 However, to the best of our knowledge, the impact of different types of surgery and RT on sexual function has not been well studied to date. It is well known that for many patients, preserving QOL is of high importance in the treatment decision-making process; specifically, prior studies have demonstrated that >50% of men consider the preservation of sexual function to be important.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that for many patients, preserving QOL is of high importance in the treatment decision-making process; specifically, prior studies have demonstrated that >50% of men consider the preservation of sexual function to be important. 3,16,17 However, to the best of our knowledge, the impact of different types of surgery and RT on sexual function has not been well studied to date. To fill this knowledge gap, we analyzed data from a diverse, prospective, population-based cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are multiple treatment options for men with localized prostate cancer which provide similar curative efficacy but differ in their impact on health-related quality of life (HRQOL) 2 ; therefore, the latter is often an important consideration in patients’ decision-making process. Many patients with prostate cancer report that choosing a treatment which allows preservation of their sexual function is highly important 3 . For example, prostatectomy has been shown to reduce erectile functioning 47 .…”
Section: Introductionmentioning
confidence: 99%